Computational analyses of CO-rebreathing methods for estimating haemoglobin mass in humans - Chada, K. E.; Bruce, E. N. (Experimental Physiology, 2012)
Measurement of haemoglobin mass (MHb) is used to quantify alterations in oxygen delivery during exercise training or acclimatization to altitude. Uptake of carbon monoxide by haemoglobin is the basis of the common non-radioactive methods to determine MHb in humans. This study used a validated mathematical model to simulate CO uptake during rebreathing protocols and to determine sources of errors in estimation of MHb. Our previously published model was validated using experimentally measured carboxyhaemoglobin levels (%HbCO) from arterial, capillary and venous blood sites of human subjects during CO-rebreathing protocols. This model was then used to simulate various CO-rebreathing protocols in 24 human subjects with known MHb. Using variables generated by the model, MHb was estimated on the basis of assumptions typically made for calculating the volume of CO bound to myoglobin, the volume of CO exhaled and the volume of CO in the rebreathing system. It was found that inaccurate estimation of the volume of CO bound to myoglobin was the major source of error in determination of MHb. Additionally, the size of the error was found to depend on the site of blood sampling because of differences in %HbCO. Regression equations were developed to improve the estimation of volume of CO bound to myoglobin, and a new protocol that is less dependent on the site of blood sampling is proposed.